Analisis Stakeholder dalam Percepatan Penggunaan Kendaraan Bermotor Listrik Berbasis Baterai di Kota Jambi - Ginting, Mhd Arham; Syarifuddin, Hutwan; Muchlis, Fuad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study analyzes the role and influence of stakeholders in accelerating the adoption of Battery Electric Vehicles (BEVs) in Jambi City, Indonesia. Using a qualitative approach with a literature study method, this research identifies and maps key stakeholders, analyzes their influence and interests, and examines the implementation of BEV policies in Jambi City. The results indicate that despite commitments from various parties, BEV implementation still faces significant challenges, particularly in terms of infrastructure, regulation, and public awareness. The Jambi City Government plays a crucial role as facilitator and regulator, but successful implementation heavily depends on effective synergy and collaboration among stakeholders. This study recommends comprehensive strategies to optimize stakeholder roles, including developing local regulations, accelerating infrastructure development, and enhancing public education. With a holistic and collaborative approach, Jambi City has the potential to become a model for successful BEV adoption in medium-sized cities in Indonesia.